Using Balanced Scorecard Approach to Analyze The Performance of Pharmacy Installation in Implementing Strategy Mapping - Firman Pribadi, Juli Santoso (European Journal of Business and Management, 2014)
This research aimed to evaluate the vision, mission, and strategy used in Pharmacy Installation ofhospital X, as they were are needed to be redefined to keep up with the changing situation. Pharmacy Installation is an important unit in a hospital because it gives the biggest contribution to the total revenue of a hospital. The analysis of work based on Balanced Scorecard in pharmacy installation ofhospital X shows that there is an increase of work in all four perspectives. However, the vision, mission, and strategy of pharmacy installation should be redefined according to the changing situation. By having new vision, mission, and strategy, key performance indicators can be made to evaluate the performance in the future